Philomachus pugnax (Scolopacidae) - Arenabalz (Freilandaufnahmen) - Sielmann, Heinz (IWF (Göttingen), 1977)
Männchen und Weibchen des Kampfläufers sind geschlechtsdimorph und gehen niemals eine Paarbindung ein. Die Männchen gründen in kleinen Trupps Balzreviere. Durch "Sich-zur-Schau-Stellen" locken sie Weibchen an. Diese sind unscheinbar gefärbt; sie suchen die Balzreviere der Männchen nur zur Paarung auf. : Courtship behaviour of Ruff and Reeve Philomachus pugnax. Male and female are sexually dimorph and never establish any pair bond between them. During the breeding season small troups of males occupy a common courtship territory; within this common territory each male defends a small area against other males. By presenting themselves males try to attract females. In contrast to the males, females are coloured inconspicuously. They visite the territories of the males only for mating.